Etiology of Bloody Diarrhea among Children Admitted to Maternity and Children ’ s Hospital-Erbil - Rabatti, Abbass A.; Rasheed, Nazdar Ezzaddin (AL-Kindy College Medical Journal, 2008)
Background: Bloody diarrhea plays a major role inmorbidity and mortality especially in developingcountries, it is usually a sign of invasive entericinfection, there is a thought that amoebic dysentery ismore common than bacillary dysentery in Iraq, andfrom 1989 to 1997 amoebic dysentery increase from20000to 550000 patients.Objectives: This study aims to:1. Outline the incidence of various infectious causes ofbloody diarrhea in Erbil district.2. Assess the effect of multiple factors like age, sex,source of water supply, etc... On the incidence ofamebic and bacillary dysentery.3. To provide baseline data for making strategic plan toreduce the diarrhoeal mortality and morbidity.Methods: A prospective case- series study wasconducted on 116 infants and children aged 2 month –12 years admitted to hospital complaining of bloodydiarrhea. Information was taken from their mothersregarding (age, sex, geographical area, feeding patternand source of water supply) , their stool have beenexamined for the presence of RBC, leukocyte, parasiticcyst and trophozoit, however blood examination wasconducted for the presence of band.Results: The results reveal 77.5% of patients were in theyounger age group (